PENINGKATAN AKTIVITAS DAN HASIL BELAJAR SISWA MELALUI PEMBELAJARAN BIOLOGI DENGAN PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM GAMES TOURNAMENT PADA MATERI SISTEM PERTAHANAN TUBUH SISWA KELAS XI DI MAN 1 MAKASSAR - Sastrawati Hasmar AR, Arni; B, Nurhayati; Mu’nisa, A (Jurnal Biogenerasi, 2023)
This study aims to determine the application of the cooperative learning model of the team games tournament type to increase the activity and learning outcomes in the body's defense system material for class XI students at MAN 1 Makassar. This research is a classroom action research. The subjects in this study were 40 students of class XI MIPA 4 MAN 1 Makassar. Methods of data collection using observation, tests and documentation. The data instruments used were observation sheets and test sheets. The data analysis technique used is quantitative descriptive data analysis with proportions. The results showed that there was an increase in the proportion of the average score of learning activeness of 25.64%, from the first cycle of 61.94% to 87.58% in the second cycle. The results of the second cycle of data analysis show that the score has reached the specified minimum criteria of 75%. There are 7 active indicators in this study and the seven indicators have reached the specified minimum criteria of 75%. Improving learning outcomes with the application of the teams games tournament learning model in cycle I, the proportion of student learning outcomes was only 8% who completed, while as many as 92% of students had not completed from 38 students. In cycle II it can be seen that students' abilities have increased with a proportion of 100% or all students are successful in their learning outcomes. The results of the second cycle of data analysis show that the score has reached the minimum completeness criterion of 75%. The conclusions of this study indicate that the application of the cooperative learning model of the team games tournament type can increase the activity and learning outcomes of the body's defense system material for class XI MIPA 4 MAN 1 Makassar. XI MIPA 4 MAN 1 Makassar”.